2023
DOI: 10.3390/children10040610
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Experiences of Bullying in the Elementary School: The Role of Gender

Abstract: The purpose of the present study was to profile bullying behaviors in elementary schools in Saudi Arabia. A secondary purpose was to examine differences in bullying behaviors across gender. Participants were 3867 fourth graders who completed surveys during the TIMSS 2019 survey. An 11-item bullying experience scale was utilized with good internal consistency reliability. Data were analyzed using latent class analysis with Mplus 8.9 to identify profiles of bullying experiences. The results indicated the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
1
1
0
1
Order By: Relevance
“…This study confirms previous findings (Craig et al, 2009;Cook et al, 2010;Gojković & Vukićević, 2011;Juan et al, 2018;Sideridis et al, 2023;Smith et al, 2019;Wolke et al, 2001) that boys are more likely to bully others than girls. On the other hand, and in line with previous studies (Li et al, 2020;Merrill & Hanson, 2016;Perlus et al, 2014;Pontes, et al, 2018;Seo et al, 2017;USDE, 2019), the findings of this study confirm that girls were exposed to bullying to a greater extent than boys.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study confirms previous findings (Craig et al, 2009;Cook et al, 2010;Gojković & Vukićević, 2011;Juan et al, 2018;Sideridis et al, 2023;Smith et al, 2019;Wolke et al, 2001) that boys are more likely to bully others than girls. On the other hand, and in line with previous studies (Li et al, 2020;Merrill & Hanson, 2016;Perlus et al, 2014;Pontes, et al, 2018;Seo et al, 2017;USDE, 2019), the findings of this study confirm that girls were exposed to bullying to a greater extent than boys.…”
Section: Discussionsupporting
confidence: 92%
“…У овом истраживању потврђени су резултати претходних (Craig et al, 2009;Cook et al, 2010;Gojković & Vukićević, 2011;Juan et al, 2018;Sideridis et al, 2023;Smith et al, 2019;Wolke et al, 2001) да су дечаци више склони испољавању вршњачког насиља него девојчице. С друге стране, у складу са претходним истраживањима (Li et al, 2020;Merrill & Hanson, 2016;Perlus et al, 2014;Pontes, et al, 2018;Seo et al, 2017;USDE, 2019), у овом истраживању је потврђено да су девојчице у већој мери биле изложене вршњачком насиљу у поређењу са дечацима.…”
Section: дискусијаunclassified
“…More studies have also found that the rate of bullying or participation in bullying is significantly higher for boys than for girls, and this difference is consistent across cultures [27,28]. Sideridis and Alghamdi [29] examined differences in bullying behaviors across gender, finding that boys were more likely to be perpetrators of forms of direct bullying, such as physical bullying. In addition, studies have found that there are gender differences in the Dark Triad [30].…”
Section: Introductionmentioning
confidence: 99%